1993
DOI: 10.1002/aja.1001970106
|View full text |Cite
|
Sign up to set email alerts
|

Regulative ability of the prospective cardiogenic and vasculogenic areas of the primitive streak during avian gastrulation

Abstract: Four types of microsurgical experiments were conducted to analyze heart and blood vessel development during gastrula stages of avian embryos, stages during which prospective cardiogenic and vasculogenic cells reside within the primitive streak. Experiments addressed whether cells not normally destined to form heart could form heart when given the opportunity to do so and vice versa; cells destined to form rostral levels of the heart (or, alternatively, head blood vessels) could form caudal levels of the heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 31 publications
3
30
0
Order By: Relevance
“…This interpretation is consistent with the findings of Gonzalez-Sanchez and Bader (1990), who observed evidence of cardiac myocyte specification at stage 4. Recent studies by Inagaki et al (1993) indicate that presumptive cardiogenic and vasculogenic cells in the primitive streak just prior to stage 4 are not determined. Also, right/left-handedness of the heart is established as early as stage 5 (Hoyle et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation is consistent with the findings of Gonzalez-Sanchez and Bader (1990), who observed evidence of cardiac myocyte specification at stage 4. Recent studies by Inagaki et al (1993) indicate that presumptive cardiogenic and vasculogenic cells in the primitive streak just prior to stage 4 are not determined. Also, right/left-handedness of the heart is established as early as stage 5 (Hoyle et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The experiments of Orts-Llorca (Orts-Llorca, 1963;Orts-Llorca and Gil, 1965), in which heart formation was inhibited following removal of anterior endoderm from stage 4-5 chick embryos, provided evidence for a n inductive influence of endoderm. More recent studies, however, have reported that removal of endoderm from stage 3 (Inagaki et al, 1993) or stage 5 (Arias et al, 1987) embryos does not inhibit heart formation. These results must be reconciled with the time lapse observations of Inagaki et al (19931, showing that endoderm regenerates following extirpation from stage 3 embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Cells that migrate anterior and lateral to the primitive streak in early gastrulation contribute to heart tissue, whereas cells that move into the posterior lateral plate form the extraembryonic blood islands (Rosenquist and DeHaan 1966;Schoenwolf et al 1992;Garcia-Martinez and Schoenwolf 1993). Precardiac cells residing in the primitive streak at stage 3 are uncommitted (Inagaki et al 1993) but become specified in response to signals from surrounding tissues after their migration into the lateral plate (Antin et al 1994;Montgomery et al 1994;Sugi and Lough 1994;Schultheiss et al 1995. The cardiac mesoderm precursors are in contact with presumptive anterior endoderm throughout their migration from the streak into the lateral plate .…”
mentioning
confidence: 99%